Verifications of Pointwise Multipliers of Relations between Weighted Bergman Spaces and Hardy Spaces (MATEMATIKA, 2012)
The justification of Pointwise multipliers from weighted Bergman spaces and Hardy spaces to weighted Bergman spaces which are Hilbert are characterized by using Bloch type spaces, BMOA type spaces, weighted Bergman spaces and tent spaces. Keywords: Pointwise multipliers; Hardy spaces; Bergman spaces; Bloch type spaces; BMOA type spaces; tent spaces. 2010 Mathematics Subject Classification: 47B38